Equipment for Preparing the Pipeline Position Butts for Welding - Lobanov, L.M.; Makhlin, N.M.; Smoljakov, V.K.; Sviridenko, A.O. (Science and Innovation, 2024)
The results of R&D works of the Paton Electric Welding Institute and its specialized departments have been presented. These works mainly concern designing the Ukrainian-made equipment for preparation of the edges and butt ends of pipeline position butts with diameter from 14 mm up to 159 mm, for the assembly, repair, and modernization of power engineering facilities, including the power units of nuclear and heat electric stations, in chemical, machine-building, petroleum and other industries.